Answer:
The answer is
. Let's learn why.
Explanation:
Newton's law of universal gravitation says;
![F_{g} =G.\frac{m_{1}.m_{2}}{r^{2}}](https://tex.z-dn.net/?f=F_%7Bg%7D%20%3DG.%5Cfrac%7Bm_%7B1%7D.m_%7B2%7D%7D%7Br%5E%7B2%7D%7D)
Here G is a universal gravitational <u>constant</u> and is measured experimentally.
Sun's gravitational pull on mercury is:
![F_{Sun-Mercury} =G.\frac{m_{sun}.3,30.10^{23}}{(5,79.10^{10})^{2} }](https://tex.z-dn.net/?f=F_%7BSun-Mercury%7D%20%3DG.%5Cfrac%7Bm_%7Bsun%7D.3%2C30.10%5E%7B23%7D%7D%7B%285%2C79.10%5E%7B10%7D%29%5E%7B2%7D%20%7D)
Therefore ![F_{Sun-Mercury} = Gm_{sun} 98,4366](https://tex.z-dn.net/?f=F_%7BSun-Mercury%7D%20%3D%20Gm_%7Bsun%7D%2098%2C4366)
Sun's gravitational pull on Earth is:
![F_{Sun-Earth} =G.\frac{m_{sun} 5,97.10^{24} }{(1,50.10^{11}) ^{2}}](https://tex.z-dn.net/?f=F_%7BSun-Earth%7D%20%3DG.%5Cfrac%7Bm_%7Bsun%7D%205%2C97.10%5E%7B24%7D%20%7D%7B%281%2C50.10%5E%7B11%7D%29%20%5E%7B2%7D%7D)
Therefore ![F_{Sun-Earth} =Gm_{sun} 265,33](https://tex.z-dn.net/?f=F_%7BSun-Earth%7D%20%3DGm_%7Bsun%7D%20265%2C33)
As a result;
![\frac{F_{Sun-Mercury}}{F_{Sun-Earth} }=\frac{Gm_{sun}98,4366}{Gm_{sun}265,33 } =0,3709](https://tex.z-dn.net/?f=%5Cfrac%7BF_%7BSun-Mercury%7D%7D%7BF_%7BSun-Earth%7D%20%7D%3D%5Cfrac%7BGm_%7Bsun%7D98%2C4366%7D%7BGm_%7Bsun%7D265%2C33%20%7D%20%3D0%2C3709)
Answer:
The object will move in the opposite direction of the force applied. - 2.
Not that simple but there are ways. Just make sure your hands can handle it
the force that the planet exerts on the moon is equal to the force that the moon exerts on the planet
Explanation:
In this problem we are analzying the gravitational force acting between a planet and its moon.
The magnitude of the gravitational attraction between two objects is given by
where
:
is the gravitational constant
m1, m2 are the masses of the two objects
r is the separation between them
In this problem, we are considering a planet and its moon. According to Newton's third law of motion,
"When an object A exerts a force (action force) on an object B, then object B exerts an equal and opposite force (reaction force) on object A"
If we apply this law to this situation, this means that the force that the planet exerts on the moon is equal to the force that the moon exerts on the planet.
Learn more about gravitational force:
brainly.com/question/1724648
brainly.com/question/12785992
#LearnwithBrainly
Answer:
Explanation:
Intensity of sound = sound energy emitted by source / 4 π d² , where d is distance of the source .
A )
Intensity of sound at 1 m distance = 60 /4 π d²
d = 1 m
Intensity of sound at 1 m distance = 60 /(4 π 1²)
= 4.78 W m⁻² s⁻¹
B )
Intensity of sound at 1.5 m distance = 60 /4 π d²
d = 1.5 m
Intensity of sound at 1 m distance = 60 /(4 π 1.5²)
= 2.12 W m⁻² s⁻¹
C )
Intensity of sound due to 4 speakers at 1.5 m distance = 4 x 60 /4 π d²
d = 1.5 m
= 4 x 60 /(4 π 1.5²)
= 8.48 W m⁻² s⁻¹
D )
Intensity of sound due to .06 W speaker must be 10⁻¹² W s ⁻² . Let the distance be d .
.06 /4 π d² = 10⁻¹²
d² = .06 /4 π 10⁻¹²
d = 6.9 x 10⁴ m .